1999
DOI: 10.1074/jbc.274.11.7157
|View full text |Cite
|
Sign up to set email alerts
|

Roles for the Troponin Tail Domain in Thin Filament Assembly and Regulation

Abstract: Striated muscle contraction is regulated by Ca2؉ binding to troponin, which has a globular domain and an elongated tail attributable to the NH 2 -terminal portion of the bovine cardiac troponin T (TnT) subunit. Truncation of the bovine cardiac troponin tail was investigated using recombinant TnT fragments and subunits TnI and TnC. Progressive truncation of the troponin tail caused progressively weaker binding of troponin-tropomyosin to actin and of troponin to actin-tropomyosin. A sharp drop-off in affinity oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 72 publications
(75 reference statements)
6
83
0
Order By: Relevance
“…These fragments of cTnT (Fig. 5A) were previously confirmed as good functional representations of that particular fragment of the protein (27). Interactions between cTnT constructs and PKA-RI, or -RII, were assessed by two different colorimetric assays, using either ␣-gal (on selective medium plates) or ␤-gal (in a colony lift assay) (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These fragments of cTnT (Fig. 5A) were previously confirmed as good functional representations of that particular fragment of the protein (27). Interactions between cTnT constructs and PKA-RI, or -RII, were assessed by two different colorimetric assays, using either ␣-gal (on selective medium plates) or ␤-gal (in a colony lift assay) (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro site-directed mutagenesis of the tail of cTnT showed that increasing elimination of residues 1 to 153 correlated with increasing to virtually complete elimination of the tropomyosin binding to actin. 28 It appears that the amino-terminal tail of cTnT is essential for assembly and anchoring of the troponin-tropomyosin complex onto the thin filament. Thus, despite mitotic and trophic simulation, the autosomal dominant inherited cTnT (Arg141Trp) acts as a poison peptide to inhibit filament assembly, which stymies the growth response.…”
Section: Discussionmentioning
confidence: 99%
“…It is expected that cardiac contractility will be impaired, because residue 141 is required for the troponin-tropomyosin complex to bind to actin. 27,28 The growth factors will most likely be upregulated, but why no growth? A likely reason stems from recent studies showing that the amino terminus (residues 1 to 153) of cTnT is essential for filament and sarcomere assembly.…”
Section: Discussionmentioning
confidence: 99%
“…Gel filtration chromatography-The standards used in calibration of the Superdex G200 HR 16/60 (GE Healthcare) column and their corresponding Stokes radii were: ovoalbumin (30.5 Å); bovine serum albumin (35.5 Å); aldolase (48.1 Å); ferritin (61 Å) and thyroglobulin (85 Å) [17,18].…”
Section: Methodsmentioning
confidence: 99%